Керамічний комплекс поселення доби пізньої бронзи Єристівка ІІ - Пефтіць, Д.М. (Сіверщина в історії України, 2020)
Статтю присвячено публікації матеріалів поселення Єристівка ІІ, дослідження якого проводилися у 2017–2019 рр. У роботі підкреслюється дискусійність культурної ідентифікації лівобережних
пам’яток доби фінальної бронзи, що актуалізує введення до наукового обігу знахідок з одношарових поселень. Такою є колекція з
розкопок Єристівки ІІ, наукова цінність якої визначається, зокрема, походженням частини знахідок із закритих комплексів. Серед
них – профільовані горщики з деформованим валиком на плічках,
миски-чаші та корчаги зі штампованим та рельєфним орнаментом. Основні типи та орнаментація керамічного комплексу дозволяють датувати пам’ятку ІХ–Х ст. до н. е. Наголошується на
тому, що посуд з культурного шару та об’єктів має близькі аналогії
серед знахідок із білогрудівських комплексів Середньої Наддніпрянщини. На основі цього матеріали з Єристівки ІІ розглядаються як
підтвердження тези про початок освоєння лівобережжя The article is devoted to the publication
of materials from the settlement of Eristivka II, the study of which was conducted in
2017–2019. The importance of introducing scientif ic f indings from single-layer
settlements is largely determined by the controversial cultural identification of the
left-bank monuments of the epoch of final bronze. Such is the collection from the
Yeristivka II excavations, some of which are from closed complexes. The kitchen utensils
are presented with pots of tulip-shaped profile, ornamented with a deformed
roller on the shoulders. Bowls-fryers belong to the same category. The
most common type of table ceramics are bowls, some of which are quite
large. Part of the collection consists of fragments of medium-sized vessels -
cups and bowls. Mostly they are thin-walled, with a well-polished surface.
Ornamented with geometric decor using stamping technique. Container
utensils are represented by fragments of large vessels, some of which
have a cylindrical neck and a rounded body. The surface of such vessels is
usually decorated with stamped or raised ornaments. A collection feature
is a series of miniature dishes of various shapes. Thus, on the basis of the
widespread types of vessels and their ornamentation, the ceramic complex
can be dated within the 9th - 10th centuries BC. It is emphasized that
the dishes have close analogies among the finds from the Bilohrudivska
complexes of the Middle Dnieper. Based on this, materials from Yeristivka
II are considered as confirmation of the thesis about the beginning of
the migration population for the left bank of the Dnieper already in the
Bilohrudivska-Belozersky time.